Tax planning for the South African emigrant to the United States, having reference to proposed & actual legislative changes in 1987-1988 - Berkowitz, Janine (Department of Commercial Law, 2026)
That approximately 40 South African citizens per day are officially emigrating to various countries is common knowledge to some and would be not surprising to many. The reasons for what may appropriately be called this 'wave of emigration' are beyond the scope of this work. Certainly the decision of each individual or household to emigrate - whether for a few years or permanently, is a personal one, whether based on, inter alia political considerations or a desire to expand their experience or expertise.